"Captive of a Scientific‐Technological Elite": Eisenhower and the Nuclear Test Ban. Issue 1 (March 2015) - Greene, Benjamin P.
<x xml:space="preserve">Abstract</x> This analysis of Dwight D. Eisenhower's pursuit of a nuclear test‐ban agreement assesses the role of science advice in his decision making. It argues that a "scientific‐technological elite" within the administration monopolized the technical conclusions in policy questions, inhibiting the president's inclination to pursue an accord with the Soviet Union for the first half of his presidency. This episode has important implications for understanding Eisenhower's record on nuclear arms control and assessments of his presidential leadership.